Manganese nitride complexes in oxidation states III, IV, and V: Synthesis and electronic structure - Kropp, Henning; King, Amanda Elisabeth; Khusniyarov, Marat; Heinemann, Frank Wilhelm; Lancaster, Kyle M.; Debeer, Serena; Bill, Eckhard; Meyer, Karsten (Journal of the American Chemical Society, 2012)
The synthesis and characterization of a series of manganese nitrides in a tripodal chelating tris(carbene) ligand framework is described. Photolysis of [(TIMEN)Mn(N)] (where TIMEN = tris[2-(3-xylylimidazol-2-ylidene)ethyl]amine) yields the isolable molecular Mn nitride, [(TIMEN)Mn(N)]. Spectroscopic and DFT studies indicate that this Mn d complex has a doublet electronic ground state. The metal-centered one-electron oxidation of this Mn species results in formation of the pentavalent Mn nitride, [(TIMEN)Mn(N)]. Unlike previously reported, tetragonal Mn nitrides with a d, nonmagnetic S = 0 ground state, this trigonal bipyramidal complex has a triplet ground state S = 1. One-electron reduction of [(TIMEN)Mn(N)] produces the neutral, nonmagnetic trivalent [(TIMEN )Mn(N)] species with a d low-spin, S = 0, ground state. © 2012 American Chemical Society.